A Cost Efficiency Study of the Housing Voucher Program as an Alternative Housing Policy for Low-Income Communities in Surabaya City - Fayza Adilah Pradani; I Dewa Made Frendika Septanaya (Jurnal Penataan Ruang, 2025)
The Government of Indonesia has implemented public rental housing (Rusunawa) program to respond to the growing housing demand among low-income communities (MBR). However, in the city of Surabaya, this program is considered inefficient due to high construction, operational, and maintenance costs, as well as limited land availability and housing units. This study aims to compare the cost efficiency between the construction of Rusunawa and the provision of Housing Vouchers as an alternative housing policy, which is widely recommended and implemented in developed countries. The method used is cost-effectiveness analysis (CEA) with a 30-year time frame (2025–2054), covering three schemes: Rusunawa construction, Housing Vouchers for lower-middle-class apartments, and Housing Vouchers for landed houses of type 36–56. The results show that Housing Vouchers for landed houses are the most efficient option, with a projected total cost of IDR 1.29 billion per household and the capacity to support up to 144 families, compared to Rusunawa (IDR 1.93 billion; 96 families) and apartments (IDR 1.83 billion; 101 families). The main challenges of this scheme include the limited availability of decent rental units and the low participation of property owners. Meanwhile, the Housing Voucher scheme for apartments is considered promising, given the high vacancy rates in the private rental housing market. This study affirms that demand-side approaches are more fiscally efficient and allow for broader beneficiary coverage compared to supply-side approaches.